Learning to work as a farming family team: Farmer responses to a gender-inclusive approach to extension - Nema, Gloria (CARE, 2019)
Presented by Gloria Nema (CARE), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.